Life cycle assessment of Organic Rankine Cycles for geothermal power generation considering low-GWP working fluids. (November 2016) - Heberle, Florian; Schifflechner, Christopher; Brüggemann, Dieter
Highlights: Life cycle assessment for geothermal energy production. Case study for German conditions. Analyses of low-GWP fluids. Comparison of various power plant concepts. Evaluation of different inventory databases. Abstract: In this study, a life cycle assessment (LCA) for geothermal power generation by binary power plants is carried out. The selected case scenarios are based on representative geothermal conditions in Germany. For this purpose, subcritical one-stage and two-stage Organic Rankine Cycle (ORC) power systems as well as supercritical cycles are considered. The LCA evaluates potential power plant concepts under consideration of working fluid losses and the associated environmental impact. Due to the restrictive regulations by the European Union for the use of fluorinated refrigerants, a special focus is laid on the evaluation of so-called low-GWP working fluids in ORC systems. In particular, the substitution of R245fa and R134a by working fluids like R1233zd and R1234yf or natural hydrocarbons is examined by a second law analysis. In addition, the environmental impact of the considered power plant concepts is calculated. The results show that the investigated low-GWP fluids lead to equivalent second law efficiency and significant lower environmental impact in comparison to common fluorinated working fluids. In case of a low-temperature heat source, the second law efficiency decreases by 2% and the global warming impact of the ORC is reduced by 78% by using R1233zd as a working fluid instead of R245fa. For the supercritical cycle with R1234yf an efficiency increase of 37% and also a significant decrease of the CO2 -equivalent is obtained. For geothermal conditions with higher temperatures of the geothermal fluid and a limitation of the reinjection temperature, like in the Upper Rhine Rift Valley, the considered optimization approaches lead to an efficiency increase of up to 7%. In this context, the concept of a two-stage ORC is favorable. Compared to a subcritical one-stage system with R245fa as a working fluid, the two-stage ORC with R1233zd leads to 2% higher exergetic efficiency and a reduction of the global warming impact from 78 gCO2 /kWhe to 13 gCO2 /kWhe .